IMPLEMENTASI PERATURAN GUBERNUR DAERAH KHUSUS IBUKOTA JAKARTA NOMOR 2 TAHUN 2020 TENTANG PENYELENGGARAAN PENGEMBANGAN KEWIRAUSAHAAN TERPADU - Pringga Arbi, Zaka; Hakim, Abdul; Haris Wanto, Alfi (Jurnal Administrasi Publik, 2025)
Implementation of the Regulation of the Special Capital Region of Jakarta Number 2 of 2020 concerning the Implementation of Integrated Entrepreneurship Development. The policy aims to empower micro, small, and medium enterprises (MSMEs) through structured support in the form of training, mentoring, legality facilitation, marketing, financial reporting, and access to financing. Using a qualitative case study method, this journal analyzes the policy content, implementation context, and its impact on MSME development. The findings indicate that the policy implementation has demonstrated success, although challenges remain, such as unequal access to benefits, limited mentoring, and centralized decision-making. Nevertheless, this policy has contributed to improving participants’ skills, legal awareness, and market access.